CONSTRUCTION OF CHARACTERISTICS CURVE TUNNEL ADVANCED USING THREE-DIMENSIONAL FINITE ELEMENT METHODE - PUTRA SUKARTO SURBAKTI (NIM : 12113070), SAMUELSON
Stabilization analysis of underground tunnel openings is important to know. Supporting system is closely related to the magnitude of the displacement experienced in the tunnel, where the displacement of rock mass and supporting is a function of time and advance of excavation. Basically, the rock mass has its own support pressure or commonly known as the internal support pressure. The failure in the opening hole occurs when the internal support pressure is smaller than the critical support pressure. This is explained because when the construction of an opening in the mass of the rock will result in redistribution of stresses around the opening and also allows the emergence of plastic zones around the openings. Then the stress which towards to the tunnel (radial stress) will be greater than before, and if the stress value is greater than the internal support pressure pressure will cause the failure. The decrease of internal support pressure will occur along with the advance of excavation. In this study we will observe the decrease of internal support pressure due to excavation progress using RS3 2.0 software. Modeling with RS3 2.0 uses finite element method. This research uses the external boundary 100x110x110 m (tunnel will be dug 100 m) with radius of opening hole 5 m. Excavations were carried out in stages with a single excavation which in RS3 2.0 would be segmented at 1 m intervals (100 stages). In the results of this study can also see the displacement that occurs every progress of the excavation. Furthermore, a graph of the Longitudinal Displacement Profile will also be displayed for the purpose of viewing the radial displacements occurring along the unsaved excavation axis (ahead of the face and behind of the face).